The Knowledge Level of Elderly in Puskesmas Taliwang and the Incidence of Chronic Kidney Disease in 2024 - Cahyani, Aulia Putri; Maulana, Akhada; Arsatt, Maz Isa Ansyori; Wedayani, Anak Agung Ayu Niti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chronic Kidney Disease (CKD) is a gradually progressing condition that frequently remains asymptomatic in it’s early stages, making it an increasingly significant public health concern, particularly among the elderly. Early awareness and preventive behavior are crucial to mitigate it’s impact, yet many elderly individuals lack sufficient knowledge about disease. This study aims to examine the relationship between the knowledge level of elderly individuals and the incidence of CKD in the Puskesmas Taliwang area in 2024. A cross-sectional analytical study was conducted involving 30 elderly participants selected through simple random sampling. Data on knowledge level were collected using a structured was performed using the Chi-square test. The result showed a significant association was found between knowledge level and CKD incidence P-value=0.000 and OR value is between 0,900 and 1,020, indicating that lower knowledge correlates with a higher risk of CKD. There is a significant relation between the knowledge level of elderly individuals and the incidence of CKD in the Puskesmas Taliwang area. Strengthening educational outreach and awareness programs is essential to reduce CKD risk among the elderly.